Frequency of Diabetic Retinopathy Amongst Type 2 Diabetes Mellitus Patients - Mubashir Rehman, Jamal Hussain, Imran Ahmad, Adnan Ahmad, Mohammad Farhan, Jawad Humayun (Pakistan Journal of Medical & Health Sciences, 2023)
Background: A chronic and debilitating condition called as diabetes is now a global epidemic problem. Patients in our population with 2 diabetes mellitus often develop diabetic retinopathy. Objective: To assess the diabetic retinopathy frequency amongst type 2 diabetes mellitus patients Methodology: The observational study was carried out at Ophthalmology, Department, Qazi Hussain Ahmad Medical Complex, Nowshera from January 2022 to July 2022. Ophthalmoscopy (Both direct and indirect) was done for the retinopathy and was then classified according to standard classification. All the data including age, gender and frequency of retinopathy was documented in a proforma designed for this research. IBM SPSS version 23 was used for data analysis. Results: In the current research, totally 320 type 2 diabetes mellitus patients were enrolled. There were 176 (55%) male patients while female patients were 144 (45%). Mean age (SD) of the enrolled patients in our study was 44 (12.5) years. The mean (SD) diabetes mellitus duration was 5.21 (2.56) years. In type 2 diabetes mellitus patients, the overall diabetic retinopathy frequency was 128 (49%). Conclusion: Our study concludes that the diabetic retinopathy prevalence is very high amongst type 2 diabetic patients. The prevalence of diabetic retinopathy is significantly increased due to lack of awareness and ophthalmic assessment. All the type 2 diabetic individuals should have routine ophthalmic evaluations. Keywords: Frequency; Diabetic retinopathy; Type 2 diabetes mellitus